1998
DOI: 10.1021/om9802820
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of OsX{NHC(Ph)C6H4}H2(PiPr3)2 (X = H, Cl, Br, I):  Nature of the H2 Unit and Its Behavior in Solution

Abstract: The hexahydride OsH6(PiPr3)2 (1) reacts with benzophenone imine to give the trihydride derivative (2). The three hydride ligands and the bidentate group of 2 are situated in the equatorial plane of a pentagonal-bipyramidal arrangement of ligands around the metallic center. In solution, two thermally activated exchange processes take place between these hydride ligands, one of them faster than the other one. The reaction of 2 with HCl leads to OsH3Cl(NHCPh2)(PiPr3)2 (3), which evolves in solution into the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
54
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 79 publications
12
54
0
Order By: Relevance
“…Lluch, Lledos and coworkers have shown that the potential energy surface for elongation or contraction of the H-H distance is remarkably flat in the case of elongated dihydrogen complexes [58][59][60][61][62]. Heinekey and coworkers state, ".…”
Section: Elongated G 2 -H 2 Complexesmentioning
confidence: 99%
“…Lluch, Lledos and coworkers have shown that the potential energy surface for elongation or contraction of the H-H distance is remarkably flat in the case of elongated dihydrogen complexes [58][59][60][61][62]. Heinekey and coworkers state, ".…”
Section: Elongated G 2 -H 2 Complexesmentioning
confidence: 99%
“…The hydrogen elimination may proceed by several α‐H abstraction steps in dinuclear intermediates to produce dihydrogen complexes. Dihydrogen complexes are known for the heavier congeners of iron, for example, the cyclopentadienylruthenium complexes [CpRu(dmpe)(H 2 )] + [dmpe = 1,2‐bis(dimethylphosphino)ethane]33,34 and [Cp*Ru(dppm)(H 2 )] + [dppm = 1,1‐bis(diphenylphosphino)methane],35,36 the cationic osmium complexes [Os(en) 2 (CH 3 COO)(H 2 )] + (en = ethylenediamine)37,38 and [Os(dppe) 2 Cl(H 2 )] + [dppe = 1,2‐bis(diphenylphosphino)ethane],39 the imine complexes [OsCl 2 (NH=CPh 2 )(P i Pr 3 ) 2 (H 2 )],40 and its ortho ‐metalated relative [OsCl{NH=C(Ph)C 6 H 4 }(H 2 )(P i Pr 3 ) 2 ] 41. These complexes possess dihydrogen ligands, the energy of which is almost independent of the H–H distance.…”
Section: Resultsmentioning
confidence: 99%
“…Related crystal structures of iron compounds have not yet been reported in the literature. For substituted phenylmethanimine coordinated dihydride complexes of osmium, see: Schloerer et al (2006); Barea et al (1998).…”
Section: Related Literaturementioning
confidence: 99%